Fertilizantes organominerais granulados no plantio e cobertura em batata - Almeida, Maikon Douglas Ribeiro (2022)
Potato (Solanum tuberosum L.) is, among the vegetable crops, the most important crop in Brazil and in the world, being among the most consumed foods. Fertilizers are essential to achieve high yields, as plants are highly demanding in terms of nutrients. Organomineral fertilizers grow in the market, promoting beneficial effects on agriculture, economy and the environment. The objective of this work was to evaluate the influence of granulated organomineral fertilizer on the development, productivity and quality of the potato crop, in cultivars Agata and Atlantic. Two experiments with the same arrangement, but with two different cultivars (Agata and Atlantic), were implanted in Cristalina GO, in the typical autumn-winter period, in dystrophic red latosols with a clayey texture. The treatments consisted of: 100, 75 and 50% of the recommended dose of mineral fertilizer; 100, 75 and 50% of the recommended dose of the organomineral fertilizer and a control (without fertilization). The following were evaluated: foliar diagnosis at 48 days after planting; relative chlorophyll index (SPAD); growth and development characteristics: number of tubers and stems, length of the longest stem, fresh mass of tubers and dry mass of stems, leaves, tubers and total; physiological parameters of transpiration and photosynthesis; productivity between classes and total; and soluble solids content for Atlantic. After analysis of variance, the means were compared using the Tukey test (P<0.05). In the cultivar Agata, leaf N, P and K levels were within or slightly above the ideal range, with lower K values for 50% organomineral in relation to the control. There was no difference in relation to chlorophyll. Fertilization with 100% organomineral provided better vegetative growth of shoots, tubers and dry mass. In terms of total productivity, the dose of 100% organomineral did not differ from 100% mineral and 75% organomineral. The latter provided a higher percentage of the Special class, with higher commercial value, in relation to 100% mineral. For Atlantic, the N, P and K levels in the leaves were ideal and did not differ. There was also no difference for the SPAD index. The 75% organomineral fertilization was proportional to 100% mineral for the growth variables, except for stem dry mass. Fertilizations 100 and 75% organomineral were similar to 100% mineral for productivity of the Special class, as well as for the total, because for this the averages of the treatments were the same. There was a higher percentage of Special class when 100% organomineral was applied and in the absence of fertilization. In both cultivars, the highest doses of fertilization reduced the rate of transpiration and photosynthesis due to saline stress. The soluble solids content for the Atlantic cultivar, as well as the productivity of the First, Second and Discard classes of both cultivars were not influenced by the different sources and doses of fertilizers. Fertilizing with 75% organomineral provided growth, development and productivity similar to 100% mineral for cultivars Agata and Atlantic, making its use viable, while greater reductions can compromise them. The 100% organomineral fertilization provided the highest yields.